2020
DOI: 10.1016/j.clinthera.2020.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Clinical Manifestations and Prognosis in Patients with COVID-19

Abstract: Purpose: The purpose of this study was to determine the risk factors associated with pneumonia, acute respiratory distress syndrome (ARDS), and clinical outcome among patients with novel coronavirus disease 2019 (COVID-19). Methods: This was a cross-sectional multicenter clinical study. A total of 95 patients infected with COVID-19 were enrolled. The COVID-19 diagnostic standard was polymerase chain reaction detection of target genes of 2019 novel coronavirus (2019-nCoV). Clinical, laboratory, and radiologic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 16 publications
(20 reference statements)
5
54
0
1
Order By: Relevance
“…The in uence of frailty (frailty score of 5 or more) upon mortality outweighed that of age in our cohort (MV model 3; OR 4.3; p=0.002 vs OR 1.03; p=0.10), possibly due to the distribution of frailty which affected patients as young as 65 years of age. Several studies have reported age as a risk factor associated with mortality (35)(36)(37), and our ndings are also supported by the recently published multicentre study in the United Kingdom showing a positive association between frailty and mortality (38).…”
Section: Discussionsupporting
confidence: 87%
“…The in uence of frailty (frailty score of 5 or more) upon mortality outweighed that of age in our cohort (MV model 3; OR 4.3; p=0.002 vs OR 1.03; p=0.10), possibly due to the distribution of frailty which affected patients as young as 65 years of age. Several studies have reported age as a risk factor associated with mortality (35)(36)(37), and our ndings are also supported by the recently published multicentre study in the United Kingdom showing a positive association between frailty and mortality (38).…”
Section: Discussionsupporting
confidence: 87%
“…The in uence of frailty (frailty score of 5 or more) upon mortality outweighed that of age in our cohort (MV model 3; OR: 4.3; p=0.002 vs OR:1.03; p=0.10), possibly due to the distribution of frailty which affected patients as young as 65 years of age. Several studies have reported age as a risk factor associated with mortality (32)(33)(34), and our ndings are also supported by the recently published multicentre study in the United Kingdom showing a positive association between frailty and mortality (35).…”
Section: Discussionsupporting
confidence: 88%
“…The in uence of frailty (frailty score of 5 or more) upon mortality outweighed that of age in our cohort (multivariate model; OR:5.1; p < 0.001 vs OR:1.03; p = 0.03). Although several studies have reported age as a risk factor associated with mortality (26)(27)(28) the association of frailty status using the clinical frailty score has not been reported to be a predictor in COVID-19 patients to date.…”
Section: Resultsmentioning
confidence: 98%